2017
DOI: 10.1002/hep.29019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of surgical interruption of the enterohepatic circulation as a treatment for pediatric cholestasis

Abstract: To evaluate the efficacy of non-transplant surgery for pediatric cholestasis, 58 clinically diagnosed children, including 20 Alagille syndrome (ALGS), 16 Familial Intrahepatic Cholestasis-1 (FIC1), 18 Bile Salt Export Pump (BSEP) disease, & 4 others with low γ-glutamyl transpeptidase disease (levels <100 U/L), were identified across 14 Childhood Liver Disease Research Network (ChiLDReN) centers. Data were collected retrospectively from individuals who collectively had 39 partial external biliary diversions (PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
65
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 36 publications
2
65
1
4
Order By: Relevance
“…Several previous case series have presented data on the outcomes of surgical management of PFIC. Unfortunately, those studies have had small numbers or lacked systematic genetic diagnoses . Our data comprise the largest set of outcomes of PEBD or LTX in genetically diagnosed PFIC.…”
Section: Discussioncontrasting
confidence: 98%
“…Several previous case series have presented data on the outcomes of surgical management of PFIC. Unfortunately, those studies have had small numbers or lacked systematic genetic diagnoses . Our data comprise the largest set of outcomes of PEBD or LTX in genetically diagnosed PFIC.…”
Section: Discussioncontrasting
confidence: 98%
“…Thus, in contrast to other cholestatic conditions for which NBD was shown to be successful in attenuating refractory cholestatic itch,2 this approach might fail in particular in the subgroup of BRIC patients with severe dysfunction of ABCB11 4, 5. Consistent with our data, a case series demonstrated that pruritus in patients with ABCB11 mutations is less likely to respond completely to partial external biliary diversion compared to carriers of ATP8B1 variants 6. Hence, for patients with BRIC type 2, we recommend extracorporeal blood purification but not NBD as treatment of choice for refractory itch.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, we found no statistically significant differences in height‐adjusted and weight‐adjusted DXA Z scores between participants with and without biliary diversion. Variable clinical response to biliary diversion significantly complicates the interpretation of the results of these analyses . Some patients may respond to biliary diversion with normalization of bilirubin and bile acids, but low intestinal luminal bile acid levels may lead to profound fat‐soluble vitamin deficiencies.…”
Section: Discussionmentioning
confidence: 99%